AMERICAN Journal of Language, Literacy and Learning in STEM Education Volume 01, Issue 7, 2023 ISSN (E): 2993-2769.: THOSE WHO SEEK PARADISE FROM A DIFFERENT LAND ARE PARTIAL. - Soatova, nodira (FILOLOGIYA UFQLARI JURNALI, 2024)
1. Soatova N. The place of Shukhrat creativity in the development of Uzbek literature of the X X century. 10.00.02-Uzbek literature Phil.fan.doct (DSc) is a diss submitted for a research degree.- Bukhara, 2023 2. Obidjan A. Forgive you Paradise / fame. In memory of contemporaries. - T.: Uzbekistan, 2008. 3. Pirimqul Kadyrov. Spiritual courage / Shukhrat. Memoirs. - T.: East 1998. 4. Shukhrat. Two mouth words about myself / selected works. Three-roof, first roof. - T.: G’.Ghulam publishing house of fiction, 1969. 5. Yakubov H. Typical conditions and typical character // East star, 1969. №3. 6. Mirvaliyev S. Uzbek novel. - T.: Science, 1969. 7. Fame. Two mouth words about myself / selected works. Three-roof, first roof. - T.: G’.Ghulam publishing house of fiction, 1969. 8. Normatov U. Magic of creativity. - T.: East, 2007. 9. Shukhrat. Don’t be told. 2 vols. 1 vol. Those looking for Paradise. - T.: Publishing house of literature and art. 10. Ziyovuddinov N. Our rural contemporaries / / Star of the East, 1969. №9. 11. Soatova N. In the novel” those who seek Paradise“, the word / / materials of the international scientific and practical conference on” current issues of Uzbek philology and problems of its teaching methodology". - T.: VNESHINVESTPROM, 2022